Management of Comminuted Mandibular Fracture Due to Ballistic Trauma Using External Fixation and Osteosynthesis Plates: Case Report and Literature Review - Pampin López, Francisco (2025)
Mandibular fractures requiring surgical management are typically treated with rigid internal fixation using osteosynthetic plates. However, in cases without viable segments for fixation, external fixation is a viable alternative. This case reports a transgender male patient with multiple gunshot wounds and a comminuted mandibular fracture. Imaging revealed severe comminution. Surgical management included external fixators and a rigid fixation plate on the mandibular lower border. This method allowed proper fracture reduction, mandibular contour restoration, and acceptable occlusion, proving to be a viable treatment option for such fractures.